The impacts of perceived trust and perceived validity on the religious electronic resource acceptance - Subiyakto, A'ang (ICIC International, 2022)
Electronic resources (e-resources) are one of the essential tools for scholars related to the easiness, readability, affordability, and accessibility of the literature type. However, many scholars are accustomed to physical literature rather than electronic one. Thus, it may affect their academic work productivity. This study aims to predict factors influencing the religious e-resource acceptance among Muslim scholars in selected Islamic higher education institutions (IHEIs) in Indonesia. The technology acceptance model (TAM) was extended by incorporating two variables, namely perceived trust and perceived validity. Approximately 269 valid survey data were analyzed using the partial least square structural equation modeling (PLS-SEM) method. Besides the findings showing that both perceived trust and perceived validity variables affected the religious e-resource acceptance from the perspectives of the Indonesian scholar’s points of view, the findings have also extended the external variable variety of TAM, in the context of the religious e-resource acceptance.